Sustratos y hongos micorrizicos arbusculares en la produccion de Nochebuena - Callejas Ruiz, B.A.=700 1 Castillo Gonzalez, A.M.; Colinas leon, M.T.; Gonzalez Chavez, M. del C.; Pineda Pineda, J.; Valdez Aguilar, L.A.
(ES, En)
Ilus., 23 ref.
Keywords: EUPHORBIA; SUBSTRATOS DE CULTIVO; MICORRIZAS ARBUSCULARES VESICULARES; HONGOS DEL SUELO; NUTRIENTES MINERALES; FLORACION; PIGMENTACION; PRODUCCION; CRECIMIENTO; MEXICO; REVISTA CHAPINGO: SERIE HORTICULTURA